The Ecology of Playful Childhood The Diversity and Resilience of Caregiver-Child Interactions among the San of Southern Africa - Takada, Akira (Palgrave Studies on the Anthropology of Childhood and Youth, 2020)
XXV, 244 p. 26 illus., 10 illus. in color.